The β subunit of the high-conductance calcium-activated potassium channel contributes to the high-affinity receptor for charybdotoxin - Hanner, Markus (The National Academy of Sciences of the USA, 1997)
Transient expression of either α or α+β subunits of the high-conductance Ca(2+)-activated K(+) (maxi-K) channel has been achieved in COS-1 cells. Expression has been studied using charybdotoxin (ChTX), a peptidyl inhibitor that binds in the pore on the α subunit. Although some properties of monoiodotyrosine-ChTX ((125)I-ChTX) binding to membranes derived from each type of transfected cells appear to be identical, other parameters of the binding reaction are markedly different. Under low ionic strength conditions, the affinity constant for (125)I-ChTX measured under equilibrium binding conditions is increased ca. 50-fold in the presence of the β subunit. The rate constant for (125)I-ChTX association is enhanced ca. 5-fold, whereas the dissociation rate constant is decreased more than 7-fold when the β subunit is present. These data indicate that functional coassembly of maxi-K channel subunits can be obtained in a transient expression system, and that the β subunit has profound effects on (125)I-ChTX binding. We postulate that certain negatively charged residues in the large extracellular loop of β attract the positively charged (125)I-ChTX to its binding site on α through electrostatic interactions, and account for effects observed on ligand association kinetics. Moreover, another residue(s) in the loop of β must contribute to stabilization of the toxin-bound state, either by a direct interaction with toxin, or through an allosteric effect on the α subunit. Certain regions in the extracellular loop of the β subunit may be in close proximity to the pore of the channel, and could play an important role in maxi-K channel function.